Kualitas Susu Segar di Kota Yogyakarta Pada Tahun 2012 - , NIKEN AYU GANDINI, Dr. drh. Yatri Drastini, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Consumer demand for dairy food availability in the region is currently Yogyakarta increases public awareness of the importance of health to consume cowâs milk. The final task aims for know the quality of fresh milk sold in the Yogyakarta city in 2012 years. Material that is used in this theisis is based on exami nation of data in veterinary public health laboratory DISPERIDAGKOPTAN yogyakarta in 2012. The test performed,test condition that include milk organoleptik ( color, smell, and taste) the clean liness test, test degr acide, alkohol test, testing as well milk composition testing that includes testing and specific gravity test lipid content. Result of testing the quality of fress milk sold of Yogyakarta city in 2012 year showed that milk is worth as much as 58,93% and 41,07% better worth enough milk. Specific average gravity is 1,0284 fress milk 3,3% lipid and 6,5 acid degrees. Circumtances indicate that the milk is milk has been circulate in Yogyakarta 2012 years worth for the consumer.